The QUALITY OF LIFE IN ADOLESCENT DURING COVID 19 PANDEMIC - Setiyawan, I Made Karma; Apsari, Ni Luh Sri; Saputra, I Made Yullyantara; Sindhughosa, Wega Upendra; Sinardja, Siska Permanasari; Mayangsari, Ayu Setyorini Mestika; Witarini, Komang Ayu; Dewi, Ida Ayu Made Ratna (Universitas Udayana, 2023)
Background : Assessment of quality of life in children is a useful indicator of overall health because it encompasses information about children's physical and mental health. Managing the existing environment and adhering to current constraints due to Covid-19 can be especially difficult for children and adolescents because these conditions can be regarded as incompatible with their developmental tasks. The Pediatric Quality of Life Inventory (PedsQL) is a tool designed to assess children's quality of life based on age, maturity, and cognitive development. While self-report is the gold standard for measuring perceived PedsQL, there may be occasions when the kid is too young, too sick, or too tired to complete PedsQL instrument, in which case a parent-proxy report may be required. Methods : An analytic observational study using a cross-sectional design involve three elementary schools in the Jimbaran area, Badung, Bali. The research was conducted at Udayana University Hospital in July 2022. Detailed explanations about the context and how to fill out the PedsQL form were given to students and their parents. The students and parents fill out PedsQL forms in separate rooms. The PedsQL questionnaire used was the Indonesian version. Concordance between self-report and parent-proxy was evaluated using the Wilcoxon paired sign rank test. Intraclass correlation coefficients (ICC) to assess parent and child agreement. Results : Amongst 189 children, median age was 11 years (range 11–13 years). There was no difference in PedsQL between self-report and parent-proxy in overall and subscales functioning domain. Physical, emotional, social, and school functioning all had intraclass correlation coefficients of 0.85, 0.83, 0.79, and 0.88, respectively. Low energy (physical functioning), feel afraid or scared and feel angry (emotional functioning), and can’t do things that children his age do (social functioning) were found different among factor loadings. School functioning factor loadings were found similar. Conclusion : This study shows a good agreement and no significant difference in overall and subscale scores between children's self-report and parent-proxy reports. Although significant differences were found when examining each factor loadings in each component.